Duhamel’s procedure for Hirschsprung’s disease and the functional outcome in a tertiary care center - K L Aravind; N Nisha; R Sushmitha; Chandrakanth Madiwal (Indian Journal of Child Health, 2021)
Introduction: Hirschsprung’s disease (HD) is a developmental disorder caused by the migration failure of neural crest cells during intestinal development, resulting in an aganglionic colon and causing a functional obstruction in children. Duhamel’s procedure (DP) which involves excision of the aganglionic segment with retrorectal pull through, and anastomosis of the ganglionated bowel above dentate line, is one of the classical surgical procedures for HD. Materials and Methods: This retrospective study was conducted in a tertiary care center in South India. The medical records and follow-up details of 17 patients, who underwent DP for HD between January 2014 and December 2018, were obtained and evaluated. Outcomes evaluated included incidence of post-operative constipation, incontinence/soiling, enterocolitis, anastomotic stricture, and leak. Results: There were 17 patients with HD who underwent DP during the study period, among which 76.47% of patients had classical HD and 23.52% were long-segment HD. A total of 58.82% of patients presented at birth, with overall 76.47% of male predominance. Fecal soiling (29.41%), perianal excoriation (17.64%), wound infection (11.76%), post-operative enterocolitis (11.76%), stricture formation (11.76%), constipation (11.76%), and hypertension (11.76%), and adhesive bowel obstruction (5.88%) were some complications observed in this study. Most of these complications were successfully managed. Conclusion: Staged DP is safe and can address the entire spectrum of HD. Complications are less and comparable to other techniques, and with close follow-up to address the post-operative complications, good quality of life can be achieved for the children with HD.